Analisis Perbandingan Kinerja Fisheye State Routing Protocol dan Greedy Perimeter Stateless Routing Protocol pada Vehicular Ad-Hoc Network dalam Lingkungan Jalan Perkotaan - Bisma Arie Yaqudsa; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Vehicular Ad-Hoc Network (VANET) is a network which the development is devoted for node in form of mobile vehicle. As the frequent changes of node compotition, it is required a routing protocol that functions to determine the proper information dispatch line between nodes. The obstacles that are often found in cities is the vehicle density, the signal transmition barrier such as concrete, buildings, as well as the interfention and varied movements of the node, therefore it is needed a proper routing protocol to maintain the data transfer efficiently. By analyzing the performance comparation of FSR and GPSR protocol, it was obtained a trial parameter in form of End-to-End Delay, Packet Delivery Ratio and Throughput so that it would be found which one is the most efficient protocol to be implemented in urban area. By the vehicle density scenario, it was found that the denser of the vehicle, the lower of the performance and trial score and it was increasing as the density of vehicle was decreased. FSR protocol has the Packet Delivery Ratio average rate for about 22.398%, End to End Delay for about 0.45s and Throughput for about 0.337kbps. Meanwhile, GPSR protocol has Packet Delivery Ratio average rate for about 25.493%, end to end delay for about 0.64s and throughput for about 0.480kbps. Based on parameter score tested, it was concluded that GPSR is better to be used in VANET in urban environment.